(untitled) (Jurnal Destinasi Pariwisata, 2025)
Social media users counted as much as 5,17 bilion in July 2024, proves that the uses of social media is increasing with relation to technological updates year by year. The uses of social media for now is just not for entertainment, but also for information yet the promotion media. For these years, the one of social media that hype a lot is TikTok, followed by the pandemic issue and the users has been increased by then. TikTok’s popularity brings us new things in many ways, like user can communicate with other user, uploading content, education media and sharing information to people. Melali Bali is one of TikTok accounts who’s provide the information about tourism, and Kelan Beach is the destination that has been promoted by them so the audiences have visual information in general about Kelan Beach before they decide to visit. Because of that phenomena, it’s necessary to explore how social media can influence tourist decision on visiting the destination, especially TikTok. This study uses statistis descriptive analysis method to know the tourist’s characteristics, also simple linear analysis to know how many effect of TikTok posts of Melali Bali account on tourist decision to visiting Kelan Beach. The research instrument used was likert scale with questionners. Based on the result this research, it found that Melali Bali’s post have siginificant influence on decision making to visit Kelan Beach. From coeffecient correlationt test, Melali Bali’s post have an influlence by 83,8% to decision making to visit Kelan Beach and the 16,2% have been influenced by other unkown reason or not yet researched.